Improving management of tuberculosis in people living with HIV in South Africa through integration of HIV and tuberculosis services: a proof of concept study - Irit Sinai; Farley Cleghorn; Hans Friedemann Kinkel (BMC, 2018)
Abstract Background South Africa's tuberculosis burden is the third highest globally and is closely associated with the country's devastating HIV epidemic. The separation of HIV and TB services in primary healthcare services in South Africa hampers TB case finding in patients who are co-infected with HIV and TB. This operational proof of concept study assessed an approach to improving tuberculosis detection and treatment by integrating tuberculosis management into HIV care. Methods The intervention involved workforce re-engineering accompanied by changes to the physical environment in three primary healthcare facilities in Gert Sibande district, Mpumalanga Province, that allowed HIV providers to test their HIV patients for TB and initiate and monitor TB treatment when indicated. To assess the proof of concept we compared the management of TB patients by HIV and TB providers, by reviewing the records of all facility patients who tested positive for tuberculosis between July 2015 and February 2016. We also considered the perceptions of healthcare providers and facility managers about the intervention through structured interviews. Results Approximately 30% of the 1855 patients with presumed TB in the three clinics had been identified by HIV providers. The percentage of patients consecutively tested for TB was 81.0% and 85.0% (p = 0.0551) for HIV and TB providers, respectively. Of the patients identified with TB by HIV and TB providers, 75.4% and 79.2% (p = 0.2876), respectively, were initiated on treatment. The defaulter rate was higher among HIV, compared to TB, providers (12.8% versus 4.2%). Overall, healthcare providers and facility managers had positive views of the intervention but raised concerns regarding potential increase in workload and administrative issues, as well as infection control. Conclusions The results of this proof-of-concept study indicate that the full spectrum of TB services can be easily and effectively integrated into existing HIV care programs. However, a possible shift in the service providers' workload, including administrative tasks, must be tackled and effective infection control must be ensured. Further research is needed to assess the impact of TB service integration into the scope of HIV care (or other chronic care programs) on patient outcomes, including analysis of routine data.